The Italian job: match rigging, career concerns and media concentration in Serie A - Tito Boeri; Battista Severgnini (Institute for the Study of Labor (IZA), 2008)
This paper contributes to the literature on competition and corruption, by drawing on records from Calciopoli, a judicial inquiry carried out in 2006 on corruption in the Italian soccer league. Unlike previous studies, we can estimate the determinants of match rigging and use this information in identifying corruption episodes in years in which there are no pending judicial inquiries. We find evidence of corruption activity well before Calciopoli. Career concerns of referees seem to play a major role in match rigging. An implication of our study is that a more transparent selection of the referees and evaluation of their performance is essential in removing incentives to match rigging. Another implication is that in presence of significant winners-take-all effects, more competitive balance may increase corruption unless media concentration is also significantly reduced.
urn:nbn:de:101:1-2008111487
Keywords: D73; 330; Concentration; corruption; career concerns; random effect ordered probit; Monte Carlo simulations; soccer; Fußballsport; Professioneller Sport; Betrug; Korruption; Wettbewerb; Schiedsgerichtsbarkeit; Karriereplanung; Medienwirtschaft; Wirtschaftskonzentration; Italien